2014
DOI: 10.1016/j.joca.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and cellular segmental characterization of human meniscus: building the basis for Tissue Engineering therapies

Abstract: Menisci are not uniform structures. Anterior segments have lower cellularity and higher damping. Cyclic loads influence viscoelastic characteristics. Future TE therapies should consider segmental architecture, cellularity and biomechanics of fresh tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 53 publications
6
59
1
Order By: Relevance
“…Generally, avascular regions were observed to be at a distance of > 5 mm from the outer periphery. The difference in 2D cellularity between the vascular and avascular regions was reported in a previous study (Pereira et al , ). In the present study, the 3D cellular densities of the vascular and avascular regions were quantified to be 27 199 and 12 820 cells/mm 3 , respectively.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Generally, avascular regions were observed to be at a distance of > 5 mm from the outer periphery. The difference in 2D cellularity between the vascular and avascular regions was reported in a previous study (Pereira et al , ). In the present study, the 3D cellular densities of the vascular and avascular regions were quantified to be 27 199 and 12 820 cells/mm 3 , respectively.…”
Section: Discussionsupporting
confidence: 68%
“…For this reason, some cells that are actually of different cell type could be identified to be from the same cell population, due to their similar morphology; for example, both a superficial zone cell and a fibroblast‐like cell have a fusiform morphology. In a previous study (Pereira et al , ), it was reported that the cell populations in the meniscus were positive for CD105, CD73 and CD90 markers and negative for haematopoietic markers, such as CD45 and CD34, as well as CD31. Quantification of the cell phenotypes and their individual densities were not within the aims of the present study, and should be a subject of further investigation using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Low fibrillar stiffness, high permeability, and reasonably high nonfibrillar matrix modulus help tissue deformations and dissipation under prolonged loading conditions. It may be that the meniscus, which was not considered here, may be the elastic shock absorber in the knee while the tibial plateau cartilage contributes primarily to the viscous dissipation of loads (Danso et al, 2015;Gaugler et al, 2014;Pereira et al, 2014).…”
Section: Discussionmentioning
confidence: 99%